E-Commerce: Goods Warehousing and Tax Avoidance - Pearce, Prafula; Pinto, Dale (2018)
Australian consumers are increasingly purchasing goods from other countries, especially through on-line platforms such as eBay. It is anticipated that global ecommerce sales will reach US$4.5 trillion by 2021 with Australia being in the top ten countries to engage in this form of trade. On-line platforms and logistic companies are increasingly providing overseas sellers with warehousing facilities in Australia and other countries to store the merchandise for faster delivery of products to on-line shoppers. They provide a local address, a warehouse and local bank account. This practice can have a substantial impact on Australian tax revenues which could in turn adversely affect local retailers. This paper examines whether overseas sellers are carrying on a business in Australia for tax and consumer law purposes in the circumstances described above. The paper also explores the shortcomings of the current Australian tax rules, and offers possible solutions.